2022
DOI: 10.1007/s44177-021-00008-8
|View full text |Cite
|
Sign up to set email alerts
|

Food Security Challenges and Options in the Caribbean: Insights from a Scoping Review

Abstract: The Caribbean region remains susceptible to an increasing frequency of natural disasters, rising international debt, out-migration, rapid urbanization, and high imports to meet basic needs. Food and nutrition insecurity persists in these small island states, with around 67.5% of the population living in moderate or severe food insecurity. Policy adjustments required to address the targets subsumed by the second sustainable development goal (SDG2 or Zero Hunger) are still at an infant stage. This research offer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…(2021) found that a systematic review had been useful in the identification of neglected areas during food safety hazard surveys. Other authors also support the idea that surveillance and epidemiological studies and active laboratory surveillance in the hospitality premises have limitations and leave gaps in the information available about foodborne diseases, sources and etiological agents which is required for proper surveillance (Hull-Jackson and Adesiyun, 2019; Mohammadi et al. , 2022; Ntshoe et al.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…(2021) found that a systematic review had been useful in the identification of neglected areas during food safety hazard surveys. Other authors also support the idea that surveillance and epidemiological studies and active laboratory surveillance in the hospitality premises have limitations and leave gaps in the information available about foodborne diseases, sources and etiological agents which is required for proper surveillance (Hull-Jackson and Adesiyun, 2019; Mohammadi et al. , 2022; Ntshoe et al.…”
Section: Discussionmentioning
confidence: 85%
“…Similarly, Torres et al (2021) found that a systematic review had been useful in the identification of neglected areas during food safety hazard surveys. Other authors also support the idea that surveillance and epidemiological studies and active laboratory surveillance in the hospitality premises have limitations and leave gaps in the information available about foodborne diseases, sources and etiological agents which is required for proper surveillance (Hull-Jackson and Adesiyun, 2019;Mohammadi et al, 2022;Ntshoe et al, 2021;Torres et al, 2021). In particular, by providing scientific evidence, the systematic mapping could facilitate governmental decisions and policy-makers and their recommendations towards undertaking food safety and risk analysis in hospitality sectors in the DR and in other regions in order to prevent threats for public health.…”
Section: Discussionmentioning
confidence: 87%
“…Informal and formal stakeholder interaction in the food production systems is necessary to assist the process of policy development and implementation at wider scale ( Mohammadi et al, 2022 ). These interactions involve the function to serve as a think tank to advise the group on emerging challenges, proposing measures to optimized interventions, and proper monitoring of the policy framework.…”
Section: Future Directions Suggestions and Challenges In Action Agendamentioning
confidence: 99%
“…With year-round acceptable temperatures and land availability challenges, the islands have endured major losses from agricultural, livestock, and shery underdevelopment (Mohammadi et al 2022).…”
Section: Introductionmentioning
confidence: 99%